CdS quantum dots-based immunoassay combined with particle imprinted polymer technology and laser ablation ICP-MS as a versatile tool for protein detection - Vaneckova, Tereza; Bezdekova, Jaroslava; Tvrdonova, Michaela; Vlcnovska, Marcela; Novotna, Veronika; Neuman, Jan; Stossova, Aneta; Kanicky, Viktor; Adam, Vojtech; Vaculovicova, Marketa; Vaculovic, Tomas (Scientific reports, 2019)
For the first time, the combination of molecularly imprinted polymer (MIP) technology with laser ablation inductively coupled plasma mass spectrometry (LA-ICP-MS) is presented with focus on an optimization of the LA-ICP-MS parameters such as laser beam diameter, laser beam fluence, and scan speed using CdS quantum dots (QDs) as a template and dopamine as a functional monomer. A non-covalent imprinting approach was employed in this study due to the simplicity of preparation. Simple oxidative polymerization of the dopamine that creates the self-assembly monolayer seems to be an ideal choice. The QDs prepared by UV light irradiation synthesis were stabilized by using mercaptosuccinic acid. Formation of a complex of QD-antibody and QD-antibody-antigen was verified by using capillary electrophoresis with laser-induced fluorescence detection. QDs and antibody were connected together via an affinity peptide linker. LA-ICP-MS was employed as a proof-of-concept for detection method of two types of immunoassay: 1) antigen extracted from the sample by MIP and subsequently overlaid/immunoreacted by QD-labelled antibodies, 2) complex of antigen, antibody, and QD formed in the sample and subsequently extracted by MIP. The first approach provided higher sensitivity (MIP/NIP), however, the second demonstrated higher selectivity. A mixture of proteins with size in range 10-250 kDa was used as a model sample to demonstrate the capability of both approaches for detection of IgG in a complex sample.
Keywords: Mass Spectrometry; Laser Therapy; Immunoglobulin G; imunoglobulin G; Sulfides; elektroforéza kapilární; kvantové tečky; myši; imunoanalýza; sloučeniny kadmia; Immunoassay; Mice; Electrophoresis, Capillary; Polymers; počítačové zpracování signálu; Signal Processing, Computer-Assisted; proteiny; Cadmium Compounds; Fluorescence; zvířata; polymery; Molecular Imprinting; Animals; Proteins; laserová terapie; sulfidy; hmotnostní spektrometrie; Quantum Dots; fluorescence; molekulový imprinting